Trade Linkages Between Malaysia and The OIC Member Countries: An Emprical Analysis on Patterns, Determinant Factors, and Prospects - Irwan Shah, Zainal Abidin (2012)
International trade has always been playing a crucial role in the process of growth and development in Malaysia. This research attempts to analyze trade relations between Malaysia and The Organization of Islamic Cooperation (OIC) member countries for the period of 1997 to 2009. It is specifically aims to evaluate Malaysia-OIC trade pattern, identifies their determinants, and evaluate their future prospects. Towards these aims, the indirect quantitative analysis method and the panel data analysis using the gravity model of trade, exports, and imports are employed. The analysis of trade pattern reveals that the OIC countries have not used all their potential and resources available to establish a strong and effective intra-OIC trade. The gravity model estimates imply, among others, the importance of size effects, level of development, level of openness, and the FDI inflows in determining trade flows between Malaysia and the OIC member countries. The major determinants of Malaysia’s exports to OIC are the size of the economies, level of openness of the economy, inflation rates, and the exchange rates. On the other hand, distance factor is not significantly influence Malaysia’s imports whereas institutions is empirically proven to be a major determinant for the Malaysia-OIC of trade, exports, and imports. Findings from the aforementioned analyses are then to be constructed by employing the SWOT analysis to investigate future prospects of trade relationship between Malaysia and the OIC member countries. Based on the findings, some policy issues are highlighted and policy recommendations are developed, such as on fostering greater engagement with the OIC member countries in the African region, accelerating the effort to establish the Islamic Common Market (ICM), liberalizing the economy further, improving strategic sectors such as the Islamic Banking and Finance, and intensifying endeavors in curbing corrupt practices.